Reliability Study of Soil Resistivity Correlation with Soil Strength Properties - Mior Mohd Tahir, Muhammad Hafiz (IRC, 2015)
Reliability study can be a very useful decision-making tool in geotechnical problems. Engineering properties of soil obtained from site investigation and laboratory testing are needed to be precise for proper design and successful construction of any structure. Borehole sampling is a common and conventional method of soil investigations which are costly, time consuming and destructive. Therefore, an alternative and quick in-situ method for soil properties assessment is needed such as electrical resistivity which is non-destructive and offers a very attractive tool for describing the subsurface properties without digging. The objective of this study is to study the correlation between soil electrical resistivity and soil strength properties. A selected area with various type of soils will be run electrical resistivity using four electrodes Wenner configuration method based on geophysics and soil science standard. Soil samples from boring will be determined for its engineering parameters and separated by soil type which are sand and clay. The analysis data from electrical resistivity will be correlated with soil properties by applying reliability analysis to determine the validity of the correlation value for probabilistic analysis. In this report, reliability analysis is done by using two methods: first, Pearson product-moment correlation coefficient which evaluates the linear relationship between two continuous variables and second, Spearman-rho-ranked-order correlation coefficient which evaluates the monotonic relationship between two continuous or ordinal variables. The Pearson and Spearman correlation can range in value from -1 to 1 to indicating the strength between the two variables. For sand, the highest correlation established was when lab resistivity correlated with pH. The regression, R2, Pearson correlation, r and Spearman correlation, rs are 0.236, -0.485 and -0.562 respectively. For clay, the highest correlation established was when lab resistivity correlated with moisture content. The regression, R2, Pearson correlation, r and Spearman correlation, rs are 0.369, -0.608 and -0.779 respectively. In conclusion, the findings of this research will helps to design more efficient management through applying simple instrument and equipment for soil investigation instead of using actual physical parameters.